P-MAPA activates TLR2 and TLR4 signaling while its combination with IL-12 stimulates CD4+ and CD8+ effector T cells in ovarian cancer - Silveira, Henrique Spaulonci [UNESP]; Lupi, Luiz Antonio [UNESP]; Romagnoli, Graziela Gorete [UNESP]; Kaneno, Ramon [UNESP]; da Silva Nunes, Iseu; Fávaro, Wagner José; Chuffa, Luiz Gustavo de Almeida [UNESP] (Elsevier, 2020)
Aims: Ovarian cancer (OC) is the most lethal gynecological malignancies and many women develop chemoresistance associated with the inflammatory process. We investigated the effects of P-MAPA and IL-12 on the inflammatory and immune responses in a chemically-induced OC model. Main methods: OCs were induced with 7,12-dimethylbenz(a)anthracene into the ovarian bursa, and the animals were given P-MAPA (5 mg/kg bw., i.p., twice a week), or IL-12 (300 ng/kg bw., i.p., one a week) for 60 days, or both P-MAPA and IL-12. Immunohistochemistry, western blot, flow cytometry, and multiplex assay were used to examine the effectiveness of immunotherapies in OC. Key findings: The combinatory therapy improved the general OC features, reducing inflammatory cells and adipocyte accumulation, in addition to revealing a soft and mobile tissue with no adherences and peritoneal implants. P-MAPA treatment increased the levels of TLR2, TLR4 and TRIF in OCs while decreasing the number of regulatory T (Treg) cells. Additionally, the association of P-MAPA with IL-12 significantly increased the number of CD4+ and CD8+ T effector cells in draining lymph nodes. Regarding the inflammatory mediators, P-MAPA enhanced the levels of the pro-inflammatory cytokine IL-17 while P-MAPA+IL-12 increased the levels of IL-1β. Treatment with IL-12 enhanced the cytokine levels of IL-17, TNF-α, IL-1β, and IL-2 in addition to the chemokine MIP-1α. Significance: We conclude that P-MAPA upregulated TLR2 and TLR4 signaling, possibly activating the non-canonical pathway, while attenuating the tumor immunosuppression. Also, the combination of P-MAPA with IL-12 improves the antitumor immunoresponse, opening a new therapeutic approach for fighting OC.
Keywords: IL-12; Immune cells; Inflammation; Ovarian cancer; P-MAPA; TLR